Analysis of past and future dam formation and failure in the Santa Cruz River (San Juan province, Argentina) - Penna, Ivanna Marina (2013)
Around 11.5*10^6 m3 of rock detached from the eastern slope of the Santa Cruz valley (San Juan province, Argentina) in the first fortnight of January 2005. The rockslide-debris avalanche blocked the course, resulting in the development of a lake with maximum length of around 3.5 km. The increase in the inflow rate from 47,000-74,000 m3/d between April and October to 304,000 m3/d between late October and the first fortnight of November, accelerated the growing rate of the lake. On 12 November 2005 the dam failed, releasing 24.6*10^6 m3 of water. The resulting outburst flood caused damages mainly on infrastructure, and affected the facilities of a hydropower dam which was under construction 250 km downstream from the source area. In this work we describe causes and consequences of the natural dam formation and failure, and we dynamically model the 2005 rockslide-debris avalanche with DAN3D. Additionally, as a volume ~24*10^6 m3 of rocks still remain unstable in the slope,we use the results of the back analysis to forecast the formation of a future natural dam.We analyzed two potential scenarios: a partial slope failure of 6.5*10^6 m3 and a worst case where all the unstable volume remaining in the slope fails. The spreading of those potential events shows that a new blockage of the Santa Cruz River is likely to occur. According to their modeled morphometry and the contributing watershed upstream the blockage area, as the one of 2005, the dams would also be unstable. This study shows the importance of back and forward analysis that can be carried out to obtain critical information for land use planning, hazards mitigation, and emergency management.